PATHOPHYSIOLOGY OF SHWASROGA W.S.R. DYSPNOEA (AYUSHDHARA, 2020)
Respiratory system is divided in two parts, as upper and the lower respiratory tract. The upper respiratory tract is consists the part like the nose, nasal cavity, nasopharynx, oral cavity, while the lower respiratory tract contains larynx, pharynx, trachea, lungs, and alveoli. Major functions of respiratory system are like conduction of the air, gaseous exchange, pulmonary circulation, excretion of the metabolic waste in the form of carbon dioxide. It directly correlates with Pranavaha srotas in Ayurveda. Pranavaha Srotas plays a vital role in maintaining the vitality of the body, not only due to movement of vital Prana in this Srotas but also as it is the major route through which the pathogens enters inside the body. Dyspnoea is the one of most important common clinical feature in respiratory disorders. It is a subjective awareness of the sensation of uncomfortable breathing. It may be of physiological, pathological or environmental origin. The pathophysiology of dyspnoea is strenuous and involves the activation of various pathways that lead to increased work of breathing, stimulus of the receptors of the upper or lower airway, lung parenchyma, or chest wall and excessive stimulation of the respiratory centre. In Ayurveda dyspnoea is directly correlates with Shwaskruchchhta. The pathophysiology, etiology and clinical presentation of dyspnoea are reviewed in this article. This definitely will help to have a comprehensive Ayurvedic view in modern medicine context and to get success in diagnosis and treatment of Shwasaroga.